1986
DOI: 10.3181/00379727-183-42424
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Effects of Vitamins A, C, and E and Selenium on Carcinogenesis

Abstract: The effects of vitamins A, C, and E and of selenium on carcinogenesis are briefly summarized and updated. These vitamins and minerals were selected because they have been studied extensively in recent years with a variety of carcinogenesis models. The consumption of vitamin A and its precursors (carotenoids) has been negatively correlated with cancer at a number of sites, particularly the lung. Animal investigations on vitamin A involvement in carcinogenesis have generally been of three types: those assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 47 publications
0
26
0
2
Order By: Relevance
“…Vitamin C is mostly known for its antioxidant capacity (Steinmetz and Potter, 1991) and its ability to prevent formation of nitrosamine and other N-nitroso compounds (Birt, 1986). In addition to β-cryptoxanthin, citrus fruits are also known for their high content of vitamin C. After adjustment for β-cryptoxanthin, the small inverse association between vitamin C intake and bladder cancer risk increased towards unity.…”
Section: Vitamins Carotenoids and Bladder Cancer Risk 981mentioning
confidence: 99%
“…Vitamin C is mostly known for its antioxidant capacity (Steinmetz and Potter, 1991) and its ability to prevent formation of nitrosamine and other N-nitroso compounds (Birt, 1986). In addition to β-cryptoxanthin, citrus fruits are also known for their high content of vitamin C. After adjustment for β-cryptoxanthin, the small inverse association between vitamin C intake and bladder cancer risk increased towards unity.…”
Section: Vitamins Carotenoids and Bladder Cancer Risk 981mentioning
confidence: 99%
“…Some studies found inverse associations with intake of specific fruits or vegetables-including carrots (139,148), Chinese flowering cabbage (139), green leafy vegetables (156), fresh soybean products (157); and citrus fruit, oranges, or tangerines (139, 140, 149)-or with dietary intake of vitamin E (144) or C (149), or serum levels of carotene (168), but there have been few detailed evaluations of dietary associations with NPC risk. The apparent protective effect of fruits and vegetables may be attributed to antioxidant effects (169), prevention of nitrosamine formation (170), and other anticarcinogenic properties (171).…”
Section: Risk Factorsmentioning
confidence: 99%
“…The protective effect of tocopherols against chemical carcinogenesis has been extensively studied in various animals models with different routes of vitamin E administration [14,20]. While tocotrienols have been reported to inhibit the growth of several transplantable murine tumors, particularly sarcoma 180, Ehrlich carcinoma, IMC carcinoma and Meth A fibrosarcoma, the tocopherols had no such effect [7].…”
Section: Discussionmentioning
confidence: 99%